Supply chain structure and constraints of a rice production community enterprise: Evidence from rural Thailand - Cavite, H. J. M.; Suwanmaneepong, S. (International Journal of Agricultural Technology, 2022)
Supply chain involves actively streamlining a business’s supply-side activities to maximize customer value and gain a competitive advantage in the marketplace. In rice production, the concept of supply chain has been explored in several studies across Thailand. However, its current supply chain structure has not been updated to keep up with the emerging constraints in production and marketing, particularly at the level of community enterprises. This study investigated the supply chain structure and constraints of Ban Nong Saeng community enterprise in Chachoengsao province, Thailand. Results revealed that a chain of five major channels comprised the Ban Nong Saeng community enterprise’s supply chain as rice moved from the farm to final consumers. This chain includes farmers, primary and final processors, dealers, and local retailers. Farmers produced rice according to Organic Thailand standards. Processors create added value to rice products through product handling, packaging, and branding. Meanwhile, distributors supply packed rice to various local outlets such as Sanam Chai Khet hospital market, Wat Phra That Wayo market, and community farmers’ market. However, among the identified constraints were inadequate postharvest management skills at the farmers’ level, lack of rice mill certification at the processor’s level and poor product packaging quality, and inadequate consumer information at the marketers’ level. This research provided the insights into how the supply chain of a rice production community enterprise worked and what improvements are needed to address the existing constraints. Future studies are recommended to formulate strategic guidelines to address each problem identified. This will guide future programs and policies by the government and private sectors